SOSIALISASI DAN DEMONSTRASI PENGOLAHAN JERAMI PADI DENGAN TEKNOLOGI BIOFERMENTASI PADA KELOMPOK TERNAK PADAJAYA DESA DALUNG - P, ARI ASTAWA.; BUDAARSA, K. (Buletin Udayana Mengabdi, 2012)
ABSTRACT This Community service was conducted in a Livestock Group “Pada Jaya”, one of the Livestock Groups located at Dalung Village. Their members are people of Banjar Tegal Jaya, Dalung Village, Kuta Utara Sub District, Badung Regency. They are mostly farmers who are still having productive farm lands with very limited extensions. Nowadays, along with the care for their cattles, they usually give their cattle green woof from natural grasses. Sometimes, they also give rice straws from their waste of rice harvest which is plentiful enough along the year. They, however only do it only if they are in difficulties of getting enough fresh natural greens. Due to this condition, therefore socialization and demonstration for rice straw process with bio-fermentation technology were held. Bio-cas is a probiotik which helps to raise digestion for the livestocks. The substances derive from the cattle’s rumen liquid consisting of bacteria from genus Ruminococcus, Bacteroides, Lactobacillus and Streptococus with the other fermentative fungi genus in a media of sugar solution to fermente the organic complex into a simple organic. With this Community Service Program, the expected result is: The members of the group or breeders have knowledge and comprehension that rice straw could be used as source of livestock woof which could be stored within 3 to 4 months with a bio-cas fermentation method. From this Program, the members of the breeder group have got appropriate knowledge in utilizing rice straw. And moreover, through the use of the fermented rice straw, the members of the group would not be in difficulties to obtain green woof source for their cattles.